High food prices: The what, who, and how of proposed policy actions - von Braun, Joachim; Ahmed, Akhter; Asenso-Okyere, Kwadwo; Fan, Shenggen; Gulati, Ashok; Hoddinott, John F.; Pandya-Lorch, Rajul; Rosegrant, Mark W.; Ruel, Marie T.; Torero, Maximo; van Rheenen, Teunis; von Grebmer, Klaus (International Food Policy Research Institute, 2008)
The complex causes of the current food and agriculture crisis require a comprehensive response. In view of the urgency of assisting people and countries in need, the first set of policy actions-an emergency package-consists of steps that can yield immediate impact:; 1. expand emergency responses and humanitarian assistance to food-insecure people and people threatening government legitimacy,; 2. eliminate agricultural export bans and export restrictions,; 3. undertake fast-impact food production programs in key areas, and; 4. change biofuel policies. A second set of actions-a resilience package-consists of the following steps:; 5. calm markets with the use of market-oriented regulation of speculation, shared public grain stocks, strengthened food-import financing, and reliable food aid;; 6. invest in social protection;; 7. scale up investments for sustained agricultural growth; and; 8. complete the Doha Round of World Trade Organization (WTO) negotiations. Investment in these actions calls for additional resources. Policymakers should consider mobilizing resources from four sources: the winners from the commodity boom among countries; the community of traditional and new donor countries; direct or indirect progressive taxation and reallocation of public expenditures in the affected countries themselves; and mobilization of private sector finance, including through improved outreach of banking to agriculture. Because of countries' diverse situations, the design of programs must be country driven and country owned. Accountability for sound implementation must also rest with countries. At the same time, a new international architecture for the governance of agriculture, food, and nutrition is needed to effectively implement the initiatives described, and especially their international public goods components. Global and national action is needed, through existing mechanisms, well-coordinated special initiatives, and possibly a special fund.